Powder, method for producing the same, and method for producing resin composition

CN116867738BActive Publication Date: 2026-10-13JGC CATALYSTS & CHEMICALS LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280016403.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-30
Publication Date
2026-10-13
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

如果绝缘材料的介电常数高,则会产生介电损耗

Benefits of technology

[0019]本发明的粉体能够实现绝缘材料的低介电常数化和低介电耗损角正切化,进而能够实现半导体传输速度的高速化和传输损耗的降低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004406948670000141
    Figure BDA0004406948670000141
  • Figure BDA0004406948670000151
    Figure BDA0004406948670000151
Patent Text Reader

Abstract

The present invention relates to a powder comprising hollow particles having a cavity inside a non-porous shell. The average particle diameter (D50) of the powder is 2.0 to 10.0 μm, and the content of fine particles having a particle diameter of less than 2.0 μm is 20% by volume or less. When the powder is suspended in water, the content of floating particles is 7.0 to 25.0% by mass, the content of suspended particles is 0 to 4.0% by mass, and the content of settled particles is 71.0 to 93.0% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to powders suitable as fillers for semiconductor insulating materials. In particular, it relates to powders comprising hollow particles with internal cavities and a non-porous outer shell. Background Technology

[0002] In recent years, information and communication technologies have been developing towards high speed and large capacity. Therefore, materials used in communication equipment require low dielectric constants (low Dk) and low dielectric loss tangents (low Df). For example, printed circuit boards (PCBs) that mount semiconductor components require insulating materials with low dielectric constants and low dielectric loss tangents. If the dielectric constant of the insulating material is high, dielectric loss will occur. Furthermore, if the dielectric loss tangent of the insulating material is high, it will not only cause dielectric loss but may also increase heat generation.

[0003] To achieve low dielectric constant and low dielectric loss tangent in insulating materials, resin materials are being developed as the main body of insulating materials. Epoxy resins, polyphenylene ether resins, and fluorinated resins have been proposed as such resin materials (see, for example, Patent Documents 1 to 5).

[0004] For such resin materials, fillers are added from the viewpoint of durability (rigidity) and heat resistance. As fillers, metal oxides such as silica, boron nitride, talc, kaolin, clay, mica, alumina, zirconium oxide, and titanium dioxide are known to be used (see, for example, Patent Document 3).

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: WO2009 / 041137

[0008] Patent Document 2: Japanese Patent Publication No. 2006-516297

[0009] Patent Document 3: Japanese Patent Application Publication No. 2017-057352

[0010] Patent Document 4: Japanese Patent Application Publication No. 2001-288227

[0011] Patent Document 5: Japanese Patent Application Publication No. 2019-172962 Summary of the Invention

[0012] The technical problem that the invention aims to solve

[0013] Among materials used as fillers, silicon dioxide excels in low dielectric constant and low dielectric loss tangent. However, due to the rapid development of high-capacity and high-speed processing in data communication, there is a further demand for lower dielectric constant and lower dielectric loss tangent.

[0014] Technical means to solve technical problems

[0015] The inventors of this invention have discovered that hollow particles that do not contain microparticles and meet specified conditions can achieve a low dielectric constant and a low dielectric loss tangent in insulating materials.

[0016] That is, the powder of the present invention comprises hollow particles with cavities inside a non-porous shell, with an average particle size (D50) of 2.0 μm to 10.0 μm, and the content of microparticles with a particle size less than 2.0 μm is less than 20% by volume. When the powder is suspended in water, the floating particles are 7.0% to 25.0% by mass, the suspended particles are 0% to 4.0% by mass, and the settled particles are 71.0% to 93.0% by mass.

[0017] Furthermore, the powder manufacturing method of the present invention includes the following steps: a first step of preparing particles by spray drying an aqueous solution of silicate alkali in a hot air stream; a second step of removing the alkali contained in the particles; and a third step of calcining the alkali-removed particles, wherein a grading step for removing tiny particles smaller than 2.0 μm is provided between the first step and the third step.

[0018] Beneficial effects

[0019] The powder of the present invention can achieve a low dielectric constant and a low dielectric loss tangent in insulating materials, thereby enabling high-speed semiconductor transmission and reduced transmission loss. Detailed Implementation

[0020] The powder of the present invention comprises hollow particles with an internal cavity and a non-porous outer shell, having an average particle size of 2.0 μm to 10.0 μm. Further, the content of microparticles with a particle size less than 2.0 μm is less than 20% by volume. When the powder is suspended in water, the floating particles are 7.0% to 25.0% by mass, the suspended particles are 0% to 4.0% by mass, and the settled particles are 71.0% to 93.0% by mass. In addition to hollow particles, the powder of the present invention may also contain a small amount of solid particles. This is because solid particles may be accidentally produced during the manufacturing of hollow particles. Since solid particles without internal cavities have a high specific gravity, they are essentially considered to be potential particles within the settling particles. Preferably, more than 90% by mass of the particles contained in the powder are hollow particles.

[0021] In this paper, particles dispersed in water when suspended are referred to as suspended particles, and particles with a lower specific gravity that float in the upper layer (near the water surface) are referred to as floating particles. Such floating particles typically have high porosity. Therefore, the more floating particles added to the resin material, the lower the dielectric constant and dielectric loss tangent of the resin product. Furthermore, generally speaking, particles with higher porosity have larger particle sizes (smaller particle sizes have lower porosity). Therefore, controlling the amount of floating particles to 7.0% to 25.0% of the total particles will control (reduce) the amount of coarse particles. Since there are not many coarse particles, the resin composition used to mold resin products (insulating materials, etc.) has good filterability and injection properties. Therefore, the surface smoothness of the molded resin product is improved. Since the porosity of microparticles is low, the dielectric constant can be reduced even without increasing the content of particles with a particle size of less than 2.0 μm (microparticles). In addition, fewer microparticles result in a smaller total surface area of ​​all particles. As a result, the dielectric constant and dielectric loss tangent can be reduced due to the decrease in the amount of SiOH groups.

[0022] Therefore, by using the powder of the present invention as a filler, the filterability and injectability of the resin composition for molding can be improved, resulting in a resin product with good surface smoothness. Furthermore, the powder with fewer fine particles exhibits lower adhesion and improved flowability. Thus, processability and dispersibility are improved.

[0023] The content of microparticles is preferably 15% by volume or less, more preferably 10% by volume or less, further preferably 5% by volume or less, and most preferably 3% by volume or less.

[0024] Because the ratio (t / d) of the particle size (d) to the shell thickness (t) of the floating particles is small, there is a tendency for the particles to have lower strength. Therefore, the particles may break down between the process of mixing the resin material and the particles and the molding of the resin product (i.e., during manufacturing). Breaking particles not only hinder the reduction of the dielectric constant and the reduction of the dielectric loss tangent, but also reduce the flowability of the resin composition, thus reducing the uniformity of the resin product (molded article) and causing porosity within the resin product. However, by controlling the amount of floating particles, particle breakage can be suppressed.

[0025] Furthermore, by controlling the amount of floating particles, it is possible to ensure the preferred characteristics of high-porosity particles (e.g., low dielectric constant and low dielectric loss tangent) while suppressing their undesirable characteristics (e.g., breakage) to a non-problematic level. The presence of small-diameter, high-porosity particles in the floating particles makes them less prone to breakage during manufacturing compared to large-diameter particles, thus significantly suppressing the undesirable characteristics of high-porosity particles overall.

[0026] The content of floating particles is preferably 8.0% to 24.0% by mass, more preferably 8.0% to 23.0% by mass, further preferably 8.0% to 22.0% by mass, and most preferably 8.0% to 15.0% by mass. Furthermore, the content of settling particles is preferably 72.0% to 92.0% by mass, more preferably 73.0% to 92.0% by mass, further preferably 74.0% to 92.0% by mass, and most preferably 81.0% to 92.0% by mass.

[0027] Furthermore, the average particle size (D50) of the powder is in the range of 2.0 μm to 10.0 μm. When the average particle size is less than 2.0 μm, the specific surface area becomes high due to the abundance of tiny particles (high SiOH group content), making it difficult to obtain excellent dielectric properties. Moreover, powders with an average particle size greater than 10 μm are unsuitable for semiconductor applications. For semiconductor applications, an average particle size of 2.5 μm to 10.0 μm is preferred, and more preferably 3.0 μm to 10.0 μm is more suitable.

[0028] Furthermore, the maximum particle size (D100) is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. The maximum particle size (D100) is preferably 10 times or less than the average particle size (D50), more preferably 8 times or less. It is usually more than 2 times, and may be greater than 5 times if the requirements of the present invention are met.

[0029] The porosity of the powder is preferably 20% by volume or more, more preferably 30% by volume or more, and even more preferably 40% by volume or more. Furthermore, it is preferably 70% by volume or less, more preferably 65% ​​by volume or less, even more preferably 60% by volume or less, and most preferably 55% by volume or less. With such a porosity, it is possible to achieve both a low dielectric constant and a low dielectric loss tangent while maintaining particle strength above a specified level, effectively suppressing particle breakage.

[0030] In this paper, silica-based particles, with silica as the main component, are suitable for constituting the powder. Therefore, in addition to silica, the hollow particles (shells) contained in the powder may also contain inorganic oxides such as alumina, zirconium oxide, and titanium dioxide. The silica content in the particles is preferably 70% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably substantially composed of only silica.

[0031] [Resin Composition]

[0032] A resin composition is prepared by adding the aforementioned powder and resin materials. This resin composition is an insulating material for electronic materials such as semiconductors. Specifically, it can be used to form copper-clad laminates, prepregs, and building films for printed wiring boards (including rigid and flexible substrates). Furthermore, it can be used in semiconductor packaging-related materials such as molding resins, molding underfills, and underfill adhesives, as well as adhesives for flexible substrates.

[0033] As the resin, curable resins commonly used in electronic materials such as semiconductors can be used. Photocurable resins are also possible, but thermocurable resins are preferred. Examples of curable resins include epoxy resins, polyphenylene ether resins, fluorinated resins, polyimide resins, bismaleimide resins, acrylic resins, methacrylic resins, silicone resins, BT resins, and cyanate ester resins. Further examples of epoxy resins include bisphenol type epoxy resins, phenolic varnish type epoxy resins, pyromellitic methyl ether type epoxy resins, epoxy resins with a biphenyl backbone, epoxy resins with a naphthalene backbone, dicyclopentadiene phenolic varnish resins, phenolic aralkyl type epoxy resins, glycidyl ester type epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, and halogenated epoxy resins. These resins can be used alone or in mixtures of two or more.

[0034] In the resin composition, powder A and curable resin B are preferably contained in a mass ratio (A / B) of 10 / 100 to 95 / 100. This allows the resin composition to maintain its flowability and other properties while fully utilizing its function as a filler. A mass ratio (A / B) of 30 / 100 to 80 / 100 is more preferably preferred.

[0035] Furthermore, the resin composition preferably contains curing agents such as phenolic compounds, amine compounds, and acid anhydrides. When using epoxy resin as the curing resin, examples of curing agents include resins having two or more phenolic hydroxyl groups per molecule (bisphenol type resins, phenolic varnish type resins, triphenolmethane type resins, methyl phenolic resins, phenolic aralkyl resins, biphenyl type phenolic resins, naphthyl phenolic resins, cyclopentadiene type phenolic resins, etc.) and acid anhydrides such as methylhexahydrophthalic acid, methyltetrahydrophthalic acid, and methylnadic anhydride. Various additives (colorants, stress relievers, defoamers, leveling agents, coupling agents, flame retardants, curing accelerators, etc.) can be added to the resin composition as needed.

[0036] The resin composition can be manufactured using methods already known. For example, a curable resin, powder, curing agent, additives, etc., are mixed and kneaded using a roller press or similar method. The resulting resin composition is then coated onto a substrate and cured by heat, ultraviolet light, or similar means.

[0037] [Powder Manufacturing Method]

[0038] The powder manufacturing method of the present invention includes the following steps: a first step of preparing particles by spray drying an aqueous solution of silicate alkali in a hot air stream; a second step of removing the alkali contained in the prepared particles; and a third step of calcining the alkali-removed particles. Between the first and third steps, a step of classifying the particles to remove microparticles smaller than 2.0 μm (classification step) is provided. Alternatively, other steps such as a drying step may be provided between each step. Through such a process, the aforementioned powder can be obtained.

[0039] Generally, when manufacturing particles by firing, it is considered preferable to perform a grading process after firing to adjust the particle size. However, in this paper, a grading process is specifically performed before firing. When firing is performed without grading, the firing process is carried out with small particles that should be removed, and these small particles are sintered together with other particles. Therefore, subsequent grading cannot remove these small particles. If grading is performed before firing, the number of small particles can be reliably reduced. This allows for more reliable achievement of low dielectric constant and low dielectric loss tangent in the particles, resulting in particles that meet the requirements of high-speed data communication. Alternatively, a grading process can be performed again after firing. Each process is described in detail below.

[0040] (First process)

[0041] In this process, an aqueous solution of silicate is spray-dried in a hot air stream to granulate silica particles. This process aims to obtain hollow particles, but it is difficult to convert all particles into hollow particles; therefore, the granulated silica particles may ultimately contain solid particles. In this case, the powder obtained through the subsequent process will also contain solid particles. However, if the powder possesses the aforementioned characteristics, the desired effect can be achieved even with the presence of solid particles.

[0042] The molar ratio (SiO2 / M2O) of the silicate base is preferably 1–5, more preferably 2–4. When this molar ratio is less than 1, due to the excessive amount of alkali, it is difficult to completely remove it even with acid washing in the alkali removal process. Furthermore, due to the increased deliquescence of the spray-dried product, it is difficult to obtain the desired hollow particles. When this molar ratio is greater than 5, the solubility of the silicate base decreases, making it difficult to prepare an aqueous solution. Even if an aqueous solution can be prepared, there are cases where hollow particles cannot be formed by spray drying.

[0043] The concentration of SiO2 in the aqueous silicate alkali solution is preferably 1% to 30% by mass, more preferably 5% to 28% by mass. Even concentrations less than 1% by mass are possible, but productivity is significantly reduced. If the concentration is greater than 30% by mass, the stability of the aqueous silicate alkali solution decreases significantly, becoming highly viscous, and sometimes spray drying is not possible. Even if spray drying is possible, the particle size distribution and shell thickness become extremely uneven, limiting the applications of the obtained particles. Sodium silicate or potassium silicate, which are soluble in water, can be used as the silicate alkali. Sodium silicate is preferred.

[0044] As a spray drying method, conventionally known methods such as the rotary disc method, the pressurized nozzle method, and the two-fluid nozzle method can be employed. In this paper, the two-fluid nozzle method is suitable.

[0045] In spray drying, the inlet temperature of the spray dryer is preferably 300℃~600℃, more preferably 350℃~550℃. Furthermore, the outlet temperature is preferably 120℃~300℃, more preferably 130℃~250℃. With these temperature settings, hollow particles can be stably obtained.

[0046] (Second process)

[0047] Next, the alkali contained in the granules obtained in the first step is removed. Neutralization with acid is a suitable method for removal. It is preferable to immerse the granules in an acid solution. At this time, the molar ratio (Ma / Msp) of the number of moles of M2O (Msp) to the number of moles of acid (Ma) in the granules is preferably 0.6 to 4.7, more preferably 1 to 4.5. When this molar ratio is less than 0.6, the amount of acid is too small relative to M2O. Therefore, the silica skeletalization of silicic acid, which is thought to occur simultaneously with alkali removal, will not occur, and the granules will partially dissolve, potentially leading to gelation of the dissolved silicic acid. Even if the molar ratio is greater than 4.7, silica skeletalization will not proceed further, and excess acid is uneconomical.

[0048] Furthermore, it is preferable to impregnate the particles (as SiO2) in an acidic aqueous solution at a concentration of 1% to 30% by mass. While alkali removal and cleaning are not problematic at concentrations less than 1% by mass, manufacturing efficiency decreases. If the concentration exceeds 30% by mass, the concentration becomes too high, reducing alkali removal and cleaning efficiency. A further preferred concentration is 5% to 25% by mass.

[0049] The conditions for immersion in the acidic aqueous solution are not particularly limited as long as the alkali is removed to the desired amount; typically, the treatment temperature is 5°C to 100°C, and the treatment time is 0.5 hours to 24 hours. Afterward, cleaning is preferably performed using conventionally known methods, such as filtration cleaning with pure water. Alternatively, the above acid treatment and cleaning can be repeated as needed.

[0050] The residual amount (mass ratio) of alkali (M) after alkali removal is preferably 300 ppm or less, more preferably 200 ppm or less, and even more preferably 100 ppm or less. By thoroughly removing the alkali in this step, particle adhesion in subsequent steps can be prevented, and the formation of sintered particles in the firing process can be prevented. Furthermore, it is known that the residual amount (content) of alkali affects dielectric properties. By thoroughly removing the alkali in this step, even when using an aqueous silicate solution as the raw material, particles with low dielectric constant and low dielectric loss tangent can be obtained.

[0051] In addition, the alkali content of the final product (the particles that make up the powder) is preferably within the above range, and is usually the same as the alkali content after the alkali removal process.

[0052] The residual alkali content is measured using an atomic absorption spectrophotometer on the substance remaining after the powder has been dissolved in acid. Na is measured when sodium silicate is used, and K is measured when potassium silicate is used. Specific details are explained in the examples.

[0053] Inorganic acids (hydrochloric acid, nitric acid, sulfuric acid, etc.) and organic acids (acetic acid, tartaric acid, malic acid, etc.) can be used as acids in this process. Inorganic acids are suitable, with sulfuric acid, which has a high valence number, being particularly preferred.

[0054] (Third process)

[0055] Next, the alkali-removed particles are calcined. The preferred calcination temperature is 600℃ to 1200℃, more preferably 900℃ to 1100℃. At calcination temperatures below 600℃, the residual SiOH groups are higher, resulting in a higher dielectric loss tangent for the particles. Therefore, even with addition to the resin, it is difficult to achieve a reduction in the dielectric loss tangent. At calcination temperatures above 1200℃, the particles tend to sinter together, easily producing irregularly shaped and coarse particles. This reduces the filterability and injectability of the liquid used to form the resin composition.

[0056] (Grading process)

[0057] By performing a grading process between the first and third processes, particles smaller than 2.0 μm can be removed. If grading is performed before alkali removal, it needs to be done immediately after granulation to prevent hollow particles from absorbing moisture (deliquescence) and agglomerating / adheding. Alternatively, if grading is performed before firing, it can be continued after alkali removal.

[0058] The grading process reduces the amount of microparticles with a diameter less than 2.0 μm to less than 20% by volume. Preferably, it is less than 15% by volume, more preferably less than 10% by volume, further preferably less than 5% by volume, and most preferably less than 3% by volume. This grading process controls the proportion of floating particles in the powder within a specified range. Furthermore, the content of microparticles and coarse particles in the final product typically does not change significantly compared to the content after the grading process.

[0059] The grading process in this classification step refers to particle size classification, which separates powders according to their particle size to achieve uniform particle size. Fluid classification is an example of this particle size classification operation. Fluid classification can be divided into dry classification and wet classification. Wet classification is performed while the particles are suspended in water. This can generate SiOH groups on the particle surface, potentially negatively affecting dielectric properties. Therefore, dry classification is preferred.

[0060] Dry classification machines can be broadly categorized in principle into gravity classifiers, inertial classifiers, and centrifugal classifiers. Inertial and centrifugal classifiers allow for more precise classification. As illustrated in this invention, examples of classifiers capable of precise classification even for light particles include the Elbow-Jet manufactured by Nippon Steel Mining Co., Ltd., the SG Septar manufactured by 3M Corporation, the Aerofine Classifier manufactured by Nisshin Engineering Co., Ltd., and the MyCrosspin manufactured by PNEUMATIC Industries Co., Ltd. Among these, the Elbow-Jet and the Aerofine Classifier are preferred.

[0061] Furthermore, a drying process can be appropriately incorporated into the manufacturing process. The drying process can be performed between the alkali removal process and the grading process, between the grading process and the firing process, simultaneously at both points, or between the alkali removal process and the firing process. Multiple drying processes can be performed as needed. Alternatively, the drying process can be performed before firing, and the grading process can be performed between the drying process and the firing process. To better enjoy the effects of the present invention, it is preferable to perform the grading process and firing after the drying process. Heating is suitable as the drying process. The drying temperature is preferably 50°C to 400°C, more preferably 50°C to 200°C. Specifically, examples include methods of drying at a low temperature of approximately 50°C to 200°C over a period of time, methods of gradually increasing the temperature to dry, and methods of drying by dividing the temperature into several stages.

[0062] Furthermore, it is preferable to perform a sieving process for the particle blocks at at least one location after drying and after firing. In addition, the particle blocks refer to, for example, particle blocks with a particle size greater than 50 μm, and a sieve with an aperture (mesh size) capable of removing such particle blocks is appropriately used.

[0063] Example

[0064] The embodiments of the present invention will be described in detail below.

[0065] [Example 1]

[0066] Hollow granules are obtained by spraying 30,000 g of a water glass aqueous solution (SiO2 / Na2O molar ratio 3.2, SiO2 concentration 24% by mass) into hot air at an inlet temperature of 400°C. The water glass aqueous solution is supplied from one of two fluid nozzles at a flow rate of 0.62 kg / hr, and air is supplied from the other nozzle at a flow rate of 31,800 L / hr (air / liquid volume ratio 63,600). The outlet temperature is 150°C (first stage). In the first stage, it is possible to obtain a small number of solid granules, but it is not necessary to remove these solid granules before proceeding to the next stage.

[0067] Next, 5000g of the hollow granules (i.e., the granules obtained in the first step) were impregnated in 32000g of a 10% by mass sulfuric acid aqueous solution and stirred for 15 hours. The concentration of the solid component (SiO2) was 10.2% by mass. Furthermore, since sulfuric acid is a divalent acid, the ratio of the molar number of the acid (Ma) to the molar number of the base (Na2O) (Msp) (Ma / Msp) was 3.3. The temperature of the dispersion was 35°C, and the pH was 3.0. After this impregnation treatment, the particles were filtered and washed with pure water (second step).

[0068] Next, the mixture was dried at 120°C for 24 hours using a dryer. After drying, it was pulverized and sieved through a 75μm sieve to remove any granular lumps.

[0069] Next, using a cyclone separator manufactured by our company, the flow rate of the powder conveyor line is set to 5 m / s for dry centrifugal classification. Particles not captured by the cyclone separator are recovered.

[0070] The recovered particles were heated at 1000°C for 10 hours to obtain powder containing hollow particles (third step). After firing, particle clumps (foreign matter) were removed using a sieve with a 150 μm aperture.

[0071] The obtained powder was added together with liquid acid anhydride "Licasid MH700 manufactured by Shin Nippon Rikka Co., Ltd." and imidazole epoxy resin curing agent "2PHZ-PW manufactured by Shikoku Kasei Co., Ltd." to liquid epoxy resin "ZX-1059 manufactured by Nippon Steel Chemical & Material Co., Ltd." Here, "ZX-1059" was added at a ratio of 100 parts by weight, "Licasid MH700" at 86 parts by weight, and "2PHZ-PW" at 1 part by weight, so that the proportion of powder in the additive (paste) was 35% by volume. The additive was pre-mixed using a planetary mill and then kneaded using three rollers to obtain a paste (resin composition). The paste was heated at 170°C for 2 hours to cure it, resulting in a 50mm×50mm×1mm plate-shaped resin molded product.

[0072] The physical properties of the powders and resin molded articles obtained as described above were measured and evaluated. The results, along with the preparation conditions, are shown in Table 1. The same procedures were performed in other examples and comparative examples.

[0073] (1) Average particle size (D50), maximum particle size (D100), and number of small particles

[0074] The particle size distribution of the powder was measured dry using a particle size analyzer (Laser MicroSizer LMS-3000 manufactured by SEISHIN Corporation). Based on the measurement results, the average particle size (D50) and maximum particle size (D100) were obtained. Furthermore, this particle size distribution was analyzed to calculate the volume proportion of particles smaller than 2.0 μm, which was used as the amount of minute particles.

[0075] (2) Alkali residue

[0076] After pretreating the powder with sulfuric acid and hydrofluoric acid, it was dissolved in hydrochloric acid, and the amount of Na was measured by atomic absorption spectrophotometry (Hitachi Z-2310).

[0077] (3) Particle density and porosity

[0078] The average density (particle density) of the particles contained in the powder was measured using the gas gravimetric method (gas gravimetric method) with an Ultrapyc1200e manufactured by Quantachrome Instruments. Nitrogen gas was used.

[0079] Based on the particle density, the porosity (%) is calculated using the formula "[2.2 - (particle density)] / 2.2 × 100". Assuming the powder is composed of silica particles, 2.2 g / cm³ is used in this formula. 3 The density of silicon dioxide.

[0080] (4) Dielectric constant (Dk) and dielectric loss tangent (Df) of the powder

[0081] The dielectric constant (Dk) and dielectric loss tangent (Df) were measured using a network analyzer (ANRITSU MS46122B) and a cavity resonator (1 GHz) via the cavity resonator perturbation method. Measurements were performed according to ASTM D2520 (JIS C2565).

[0082] (5) The ratio of floating particles, suspended particles and settled particles when suspended in water

[0083] First, the powder and water were mixed to a concentration of 5% by mass and then subjected to ultrasonic treatment for 10 minutes. The resulting dispersion was allowed to stand at 25°C for 24 hours, after which floating particles, suspended particles, and settled particles were recovered separately. Next, each particle was dried at 105°C for 24 hours, and its proportion was calculated.

[0084] (6) Dielectric constant (Dk) and dielectric loss tangent (Df) of the resin molded product

[0085] The dielectric constant (Dk) and dielectric loss tangent (Df) of a 50mm × 50mm × 1mm plate-shaped molded body (resin molded part) were measured at 9.4 GHz using a network analyzer (ANRITSU MS46122B) and a coaxial resonator. Comparison with resin molded parts without added powder (filler) was performed using the following formula, and the results were evaluated according to the following criteria.

[0086] The rate of decrease in dielectric constant (Dk) (%) = (Dielectric constant without powder addition - Dielectric constant with powder addition) / Dielectric constant without powder addition × 100

[0087] 〇: Reduction rate > 0

[0088] Δ: Reduction rate = 0

[0089] ×: Reduction rate < 0

[0090] The reduction rate (%) of dielectric loss tangent (Df) = (Dielectric loss tangent without powder addition - Dielectric loss tangent with powder addition) / Dielectric loss tangent without powder addition × 100

[0091] ◎: Reduction rate of over 50%

[0092] 〇: Reduction rate of 30% or more but less than 50%

[0093] Δ: Reduction rate of 20% or more but less than 30%

[0094] ×: Reduction rate less than 20%

[0095] [Example 2]

[0096] In the classification process, a dry inertial classification process was performed using an Elbow-Jet (EJ-15) manufactured by Nippon Steel Mining Co., Ltd. This apparatus can classify powder into three types: F powder (micro powder), M powder (fine powder), and G powder (coarse powder). At this time, the edge distance of the F powder was adjusted so that the number of tiny particles smaller than 2.0 μm in the M powder (fine powder) was less than 2% by volume. The M powder was then recovered for subsequent processes. Otherwise, the powder and resin molded articles were prepared in the same manner as in Example 1.

[0097] [Example 3]

[0098] In the grading process, dry centrifugation (semi-free vortex) was used to grade the powder using an Aerofine Classifier manufactured by Nissin Engineering Co., Ltd. Grading was performed by adjusting blade angles, etc., to ensure that the recovered powder contained less than 20% by volume of microparticles smaller than 2.0 μm. Otherwise, the powder and resin molded articles were prepared in the same manner as in Example 1.

[0099] [Example 4]

[0100] The blade angle and other parameters were adjusted to ensure that the recovered particles contained less than 10% by volume of microparticles smaller than 2.0 μm. Otherwise, the powder and resin molded articles were prepared in the same manner as in Example 3.

[0101] [Comparative Example 1]

[0102] No grading process (grading procedure) was performed; otherwise, the powder and resin molded articles were prepared in the same manner as in Example 1.

[0103] [Comparative Example 2]

[0104] In the first step, the inlet temperature of the spray dryer was changed to 250°C, and in the second step, the impregnation and stirring time was changed to 1.5 hours. Furthermore, no grading process was performed. Otherwise, the powder and resin molded articles were prepared in the same manner as in Example 1.

[0105] [Comparative Example 3]

[0106] In the first step, the inlet temperature of the spray dryer was changed to 420°C, and no grading process (grading step) was performed. Otherwise, the powder and resin molded articles were prepared in the same manner as in Example 1.

[0107] [Comparative Example 4]

[0108] The grading process (grading step) is performed after firing. Otherwise, the powder and resin molded articles are prepared in the same manner as in Example 1.

[0109]

[0110]

Claims

1. A powder, characterized in that, The powder contains more than 90% by mass of hollow silica particles with a non-porous outer shell and an internal cavity. The average particle size D50 of the powder is 2.0 μm to 10.0 μm, and the content of tiny particles with a particle size smaller than 2.0 μm is less than 20% by volume. The particles contained in the powder all contain more than 70% by mass of silicon dioxide. When the powder is suspended in water, the percentage of floating particles is 11.6% to 22.0% by mass, the percentage of suspended particles is 0% to 4.0% by mass, and the percentage of settled particles is 77.4% to 87.9% by mass. The proportions of floating particles, suspended particles, and settled particles when suspended in water are measured using the following methods: The powder and water were mixed to achieve a concentration of 5% by mass and subjected to ultrasonic treatment for 10 minutes. After the resulting dispersion was allowed to stand at 25°C for 24 hours, floating particles, suspended particles and settled particles were recovered separately. After drying each particle, their proportions were measured.

2. A method for manufacturing a resin composition, characterized in that, Add the powder as described in claim 1 to the resin material.

Citation Information

Patent Citations

  • Tetrafluoroethylene resin molding material excellent in high-frequency electrical properties

    JP2001288227A

  • Polyphenylene ether resin composition, prepreg, laminate

    JP2006516297A

  • Prepreg

    JP2017057352A

  • Fluorine resin material, fluorine resin material for high frequency transmission, and coated wire for high frequency transmission

    JP2019172962A

  • Epoxy resin composition, prepreg using the epoxy resin composition, metal-clad laminate, and printed wiring board

    WO2009041137A1